Village By The Sea - Desai, Anita (Gurugram Penguin Random House India, 1984)
A Classic of Our Time. Untouched by the twentieth century, Thul, the small fishing village near Bombay, is still ruled by the age-old seasonal rhythms. Hari and Lila have lived in the village all their lives, but their family is now desperately down on its luck. Their father drinks; their mother is seriously ill; and there is no money to keep them fed and clothed. Delicately and exquisitely executed, Anita Desai$1 (Bs gentle and probing story traces the evolution of Hari and Lila into adults as each of them faces the family's predicament - just as the first signs of industrial India creep into their village.s
Keywords: Fiction